Chinese aid and social ties in Africa: Evidence from sub-national aid projects - Abreham Adera (Cogent Economics & Finance, 2023)
Is there any possibility that foreign aid may negatively affect African social ties? To answer such a question, this paper examines the impact of local Chinese aid projects on social capital in Africa. China or Chinese contractors directly control or operate Chinese projects in Africa. This feature may disengage Africans from participating in their own local development activities. Likewise, China gives unconditional aid, which may nurture corruption. By creating losers and winners, corruption may make people unhappy. Because of these features, Chinese aid projects may hinder the formation of social capital. This paper puts this claim to an empirical test using data from the Afrobarometer surveys and AidData. Conditional on a set of controls, I find several interesting results. First, Chinese aid is negatively associated with generalized trust. Second, Chinese aid projects are related to disengagement from associational life. Third, no similar pattern is found when the main analysis is replicated on aid from the World Bank. Finally, neither the Chinese nor the World Bank's aid is related to subjective wellbeing. The results suggest that Chinese aid may wither local social ties through social disengagement. Overall, the findings imply that it is vital to engage local citizens in the design and implementation of Chinese aid projects.
Keywords: 330; Africa; Chinese aid; social capital; social engagement